Pedagogy, Art, Image and Comics. A re-approach in how we teach and learn about our rights and the law - Caicedo Tapia, Danilo (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The assessment made is based on several sources of criticism to the traditional way of educating, in particular, against dogmatism, the excessive formalism, and the exclusive use of the master class as a teaching methodology, in accordance with the growing lack of understanding about education from a critical perspective. In order to overcome the beforehand explained defects, they were introduced as an alternative four scenarios – artistic, narrative, sentimental and visual – whose incorporation I consider necessary, in general to educate in the actual world, and in specific, for the teaching of rights and the law.In addition, for the mentioned scenarios, there are conceptual foundations of the educational practice: the principles regarding human dignity, liberty, equality and solidarity, not to exclude also principles from the Andean philosophy such as «Sumak Kawsay». These foundations hold the concept of education understood as a right and a way to obtain other rights. Finally, it is concluded that for education to fulfill a transformative and committed purpose with the most vulnerable, the bond with critical theories and due process of law is essential.
Keywords: Education; rights education; legal education; learning; teaching; critical theory; due process of law